Analysis Of Work Communication At PT Mikdad Perkasa Abadi Sumedang - Pratami, Yessika Meira; Royani, Solihin; Kurniawan, Ryan Feryana (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
Effective work communication plays an essential role in supporting smooth operations and maintaining professional relationships within a company. This study aims to analyze work communication at PT Mikdad Perkasa Abadi Sumedang. The research method used is descriptive qualitative with a field study design, conducted through in-depth interviews with five informants selected using purposive sampling. The main instrument in this research is the researcher, assisted by an interview guide, and the data were analyzed through data reduction, data display, and conclusion drawing using the Miles and Huberman model. The results show that communication between employees and superiors takes place through various media, such as face-to-face meetings and whatsapp, using adaptive delivery strategies, communication among employees is open and supports team collaboration, communication with investors is maintained through transparent reporting and annual forums, and communication with consumers is carried out responsively via social media and direct services